Analysis of the Consumptive Behavior of Generation Z in Surabaya Moderated by Self Control - Rachmasari, Shanti Septiana; Wikartika, Ira (Amkop Management Accounting Review (AMAR), 2025)
This study aims to examine the effect of a cashless society, social environment, and cognitive dissonance on the consumptive behavior of Generation Z in Surabaya, with self-control as a moderating variable. A quantitative method is employed in this study, involving 100 respondents as the sample. The analytical method applied is PLS-SEM, facilitated by the SmartPLS 4.0 software. The findings indicate that the cashless society, social environment, and cognitive dissonance have an impact on consumptive behavior. Self-control is found to moderate the relationship between the cashless society and cognitive dissonance with the consumptive behavior of Generation Z in Surabaya. However, self control cannot moderate the influence of the social environment on the consumptive behavior of generation Z in Surabaya. These results show that cognitive dissonance experienced by a person can strengthen consumptive behavior as a form of coping mechanism to reduce perceived discomfort. In addition, the results also reveal that the social environment is a dominant factor in encouraging the consumptive behavior of generation Z in Surabaya, even individuals with self control.